PELATIHANPENYEMPURNAAN PRODUK PEYEK REBON - Sarastri Mumpuni (UII, 2013)
Brittle or dent is a type of food or fried cakes that can be served and enjoyed witha variety of dishes. Dent can be enjoyed straight as a snack or light meal, as a friend toeat rice crackers, or presented as supplementary material variations pecal, gado-gadoand salad. In Indonesia shrimp varies in its processing, and one of them is fairly simple iswhat is called peanut brittle shrimp. Most of the New Turkish traders have a sidebusiness producing and selling Peyek Rebon that serve New Turkish specialties. Thisactivity is the provision of additional insight for culinary entrepreneurs in particular NewTurkish businessmen rebon dent dent rebon regarding product enhancements. Thepurpose of this program is to provide additional insight to the people in the hamletNgentak about product enhancements Peyek Peyek Rebon Rebon so typical of NewTurkish can provide different characteristic. This activity is carried out by means ofdiscussion regarding the identification of product enhancements Peyek Rebon, givingeducation about product enhancements Peyek Rebon and assisting citizens in thepractice of making direct Rebon Peyek that time is about 2 hours each meeting.Programs implemented to run well, although there are obstacles and constraints faced isthe lackof a culinary mothers in producing dent rebon.